Effectiveness of glucocorticoids in orthognathic surgery: an overview of systematic reviews. Issue 2 (February 2022) - Bravo, M.; Bendersky Kohan, J.; Uribe Monasterio, M.
Abstract: For decades, short-term glucocorticoids have been advocated to reduce postoperative swelling, pain, trismus, and nausea and vomiting in patients experiencing maxillofacial surgeries. The purpose of this systematic overview was to identify and assess the best evidence regarding the efficacy of glucocorticoid administration in patients who undergo orthognathic surgery. Five databases (Medline, Embase, The Cochrane Library, Web of Science, and Epistemonikos) were searched from their inception to October 2020. The risk of bias assessment was performed using the ROBIS tool, and the quality of the evidence reported was rated using the GRADE approach. Six systematic reviews were identified, of which three were included in this overview (n=527). According to the rating of the overall risk of bias, one achieved a low score and two were rated as high. The quality of the evidence reported ranged from very low to moderate. Corticoids may reduce the incidence of moderate or severe postoperative nausea and vomiting in the early postoperative period (0-6 hours) compared to metoclopramide, but the evidence is very uncertain. Some significant therapeutic effects on neurosensory recovery have been reported, but there was inconsistency across the studies. Finally, based on a moderate quality of evidence, it is possible to establish that the administration of glucocorticoids is likely to reduce oedema in the early postoperative period (0-48 hours) in patients who undergo orthognathic surgery, and to have no significant adverse effects. Further quantitative syntheses based on well-designed and standardised clinical studies are suggested to determine direction and strength of the intervention on the other outcomes.